Effects of simulated augmented reality cueing in a virtual navigation task - Stefanucci, Jeanine K.; Brickler, David; Finney, Hunter C.; Wilson, Emi; Drew, Trafton; Creem-Regehr, Sarah H. (Frontiers in Virtual Reality, 2022)
Navigational tools are relied on to traverse unfamiliar grounds, but their use may come at a cost to situational awareness and spatial memory due to increased cognitive load. In order to test for a cost-benefit trade off in navigational cues, we implemented a variety of navigation cues known to facilitate target search and spatial knowledge acquisition of an urban virtual environment viewed through an HTC VIVE Pro. We used a detection response task (DRT) during the navigation task to measure cognitive load and situational awareness. Participants searched for targets in the city with access to a map that did or did not have a "you are here" indicator showing the viewer’s location as they moved. In addition, navigational beacons were also present or absent in the environment as well as a compass and street name indicator. Participants searched for three separate target objects and then returned back to their starting location in the virtual world. After returning home, as a measure of spatial knowledge acquisition, they pointed toward each target from the home location and pointed to home and to the other targets from each target location. Results showed that the navigational cues aided spatial knowledge without increasing cognitive load as assessed with the DRT. Pointing error was lowest when all navigational cues were present during navigation and when pointing was done from home to the target objects. Participants who received the "you are here" indicator on their map consulted the map more often, but without detrimental effects for the acquisition of spatial knowledge compared to a map with no indicator. Taken together, the results suggest that navigational cues can help with spatial learning during navigation without additional costs to situational awareness.